(untitled) (Journal of Human Sciences, 2023)
This study aimed to explain the importance of attending the image in the school book in understanding the content of the texts of the Arabic language in general, and its role in understanding the spoken text in particular in the Arabic language book for the third year of primary education, through an applied study in which the descriptive analytical approach was adopted; After the importance of the school book was highlighted, the research monitored the description of the reality of the images used in this book, which came varied between manual drawings and photographs, and others were oily images in light colors that attract the attention of the learners, and then an applied lesson for spoken understanding was presented, indicating the importance of the images Accompanying him in understanding the learners of the text, and then their attempt to accomplish an oral expression using the rest of the images listed in a paragraph: produced orally, through which the research came to the fact that the images used in this book in general, and in the paragraph of spoken understanding - according to their role in provoking the element of suspense and attracting Attention- It is of great importance in understanding the learners of the operative text, and a contribution to expanding their imagination to express it in various classical Arab methodsfirst deals with the relationship between the abstract language and the theory of communication and influence. The second, on the other hand, focuses on presenting the technical procedures for the cognitive theorizing in educational schools.